The Diversity of Reef Fish in Ulee Kareung waters, Bireuen District Indonesia - Dedi Fazriansyah Putra; Muhammad Redha Subqi; Muhammad Nasir; Syahrul Purnawan; Ichsan Setiawan; Elzein Muhammed Fahal (UIN Sunan Gunung Djati Bandung, 2022)
Indonesia has abundant underwater natural resources, including coral reefs. Among coral reef ecosystems, reef fish make an important contribution to supporting the sustainability of underwater life. The more diverse reef fish in an ecosystem, it shows the healthier the condition of the coral reef ecosystem. The objective of the study was to investigate the diversity of the reef fish community including abundance, diversity, evenness, and dominance index in Ulee Kareung waters, Simpang Mamplam Sub-district, Bireuen District, Indonesia. We used a visual census technique (VCT)-belt transect by using a 50-meter transect and 3 times repetition at three observation stations. Each station had 2 depth categories such as shallow waters (3-5 m) and deep water (7-10 m). Results of the study found a total of 2094 individuals that consisted of 19 families and 59 species. The abundance value of reef fish ranged from 321 ind/ha - 610 ind/ha. The diversity index (H') ranged from 2.80 to 3.16. The evenness index (E) ranged from 0.79 to 0.88 and the dominance index (C) ranged from 0.06 to 0.10. Hence, it can be concluded that ulee kareung waters have a medium level of fish diversity.